Relationship Between Sex Ratio and Ecosystem in Lampreys Based on Logistic Model - Gao, Yujun; Zhang, Bin (Transactions on Environment, Energy and Earth Sciences, 2024)
In order to clarify the ecological ramifications of adaptive sex ratio fluctuation in lampreys, this study explores the dynamics of the population and its sex ratio using a logistic model. With the use of simulation methods and observational data, the study builds a comprehensive model to evaluate how changes in the sex ratio affect the ecosystem. With skill, the logistic model is used to forecast changes in the population of lampreys, accounting for the impact of food supply on the larval stage and subsequent determination of sex. Using MATLAB for data processing and visualization, the study further combines agent-based modeling (ABM) to replicate lamprey behaviors and their environmental interactions. Through an analysis of how sex ratio affects resource competition, predation, and population dynamics, the study sheds light on the ecological implications of changes in sex ratio in lampreys. The consideration of the ecosystem’s stability in light of changes in the sex ratio and the possible advantages for parasitic ecosystems in the paper’s conclusion lays the groundwork for further ecological and conservation research.